Budgeting in France - Moretti, Delphine (OECD Publishing, 2018)
During the last two decades, France introduced a series of far-reaching reforms intended to bring about greater transparency towards Parliament, autonomy and flexibility to public managers, and rigor in to fiscal policy making
Keywords: Finance and Investment; Governance; Economics; France